Inappropriateness of Prohibiting Appealing an Arrest Warrant - Sadradze, Tamar (Journal of Law, 2022)
According to Paragraph One of Article 13 of the Constitution of Georgia, human freedom shall be protected. The XVIII Chapter of the Criminal Procedure Code of Georgia specifies the grounds for criminal prosecution, detention and recognition as an accused. The present article deals with some problems related to a person’s detention by a court decision. It discusses the following issues: the concept and essence of detention, the gaps associated with arrest warrants, in particular the lack of legal grounds for specifying the term of execution of an arrest warrant, lack of control over the execution of an arrest warrant, the constitutional claim filed by my colleagues and me related to the prohibition of appealing an arrest warrant and resultant legal problems. The article also explores the court practice regarding a person’s detention by a court decision, which demonstrates and illustrates the problems related to detention practices. Examples of some foreign jurisdictions for appeals of warrant orders that have chosen the principles of equality and adversariality of the parties as their primary guiding principle are also discussed. The article describes the effective legal norm, reviews the judicial practice, gives conclusions and essential recommendations to improve the issue of legislative control.